Pelaksanaan Program Gerakan Literasi Sekolah (GLS) di SDN 014 Kota Bangun - Yuliyati, Devi; Dafit, Febrina (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2021)
This study aims to determine the implementation of the School Literacy Movement (GLS) program at SDN 014 Kota Bangun, Tapung Hilir District, Kampar Regency. The research method used is descriptive qualitative using interview, observation and documentation techniques with predetermined informants, namely the principal, vice principal, class teacher, and student representatives. The results of this study indicate that literacy activities at SDN 014 Kota Bangun cannot be said to be a entrenched habit, but have been included in efforts to foster a literacy culture. Although there have been other efforts in the form of literacy development and learning in each subject as an advanced stage of the implementation of the school literacy program carried out by teachers, it has not been carried out consistently and sustainably. interest. There are supporting factors, including good cooperation between schools and parents, even parents also provide input in making reading corners. There are inhibiting factors, among others, regarding the facilities and infrastructure to support literacy activities, the problem of participation of some teachers, and the activity of some classes.